Laser cooling of a ytterbium-doped silica optical fiber glass preform - Mobini, Esmaeil; Rostami, Saeid; Peysokhan, Mostafa; Albrecht, Alexander; Kuhn, Stefan; Hein, Sigrun; Hupel, Christian; Nold, Johannes; Haarlammert, Nicoletta; Schreiber, Thomas; Eberhardt, Ramona; Tünnermann, Andreas; et al. (Optics InfoBase Conference Papers, 2020)
We report the successful laser cooling of a Ytterbium-doped silica optical fiber glass preform by 0.7K relative to the room temperature. The observed temporal behavior of cooling agrees well with the theoretical predictions.
CRIS-Team Scopus Importer:2023-04-20